Integration of wheelchair service provision education: current situation, facilitators and barriers for academic rehabilitation programs worldwide. (3rd July 2020) - Fung, Karen; Miller, Taavy; Rushton, Paula W.; Goldberg, Mary; Toro, Maria L.; Seymour, Nicky; Pearlman, Jonathan; ,
Abstract: Purpose: An estimated 75 million people with disabilities need wheelchairs globally, of whom 5–15% have one. Access to an appropriate wheelchair requires rehabilitation professionals trained to provide wheelchair service. One aim of the International Society of Wheelchair Professionals (ISWP) is to promote and facilitate the integration of wheelchair service provision education into academic rehabilitation programs worldwide. To inform the development of integration strategies, the purpose of this study was to develop an in-depth global portrait of the wheelchair service provision education offered in academic rehabilitation programs, the process of its integration and the associated facilitators and barriers. Method: Semi-structured qualitative interviews were conducted with a purposive sample of 14 representatives from academic rehabilitation programs (i.e., occupational therapy, physical therapy, and prosthetics and orthotics) in 11 countries, including low, middle and upper resourced settings. Findings: Thematic data analyses identified three overarching themes. The first theme, "impact of context", portrays factors related to local population needs, governance and supply chain of equipment and service delivery. The second theme, "current and planned wheelchair education", describes the content, pedagogic approach, student evaluation and feedback process. The third theme, "integration process", details five states of this process. Conclusions: This study describes in-depth the wheelchair service provision education across academic rehabilitation programs and resource settings, illustrating the context-dependent nature of its integration. This understanding may assist the global community of educators in preparing future rehabilitation professionals to better serve wheelchair users. This work has informed the development of ISWP's Seating and Mobility Academic Resource Toolkit (http://smart.wheelchairnetwork.org/ ). Implications for Rehabilitation: The Dynamics of Context-Dependent Integration of Wheelchair Service Provision Education in Curricula model, depicting the findings of this study, may help to inform key stakeholders (i.e., academic institutions, health care providers and policy makers) about potential barriers and facilitators to the implementation of adequate wheelchair service provision education in the curricula of academic rehabilitation program. Study findings may lead to creative strategies, such as the expansion of ISWP's Seating and Mobility Academic Resource Toolkit (SMART; http://smart.wheelchairnetwork.org/ ), that may enable academic rehabilitation programs to be a part of the solution to strengthening rehabilitation systems worldwide, through appropriately trained rehabilitation professionals in wheelchair service provision.